Application of Concatenated Arterialized Venous Flaps in Finger Reconstruction. Issue 3 (March 2019) - Lin, Yu-Te; Loh, Charles Yuen Yung
Abstract : Abstract: Venous flaps from the distal volar forearm are said to be suitable flaps for finger reconstruction. The pliability of the forearm venous flap makes it easy to follow the curvature of the finger contour. The thickness of the flap makes it appropriate as a flap for finger resurfacing. Following the venous network at the palmar forearm, diverse patterns of the venous flaps can be designed. This article describes the use of a 2-concatenated paddle, flow-through arterialized venous flap design for simultaneous resurfacing of 2 separate defects on a single digit. A technique that can be used to reduce postoperative venous congestion will be highlighted in this article.